Selection of relevant features using the k-nearest neighbor classifier/application on medical images - moussaoui, mohammed elhachemi; lehimeur, elhabib (جامعة الوادي University of Eloued, 2019)
"ملخص: لقد أصبح تحليل البيانات في مجال الطب الأكثر شيوعًا من أجل تحديد التشخيص وصقل أساليب البحث وتطوير اللوازم و المعدات المناسبة اعتمادا على المعلومات المستخرجة من التصوير الطبي للأمراض التي تظهر, لتحليل البيانات من أجل التنبؤ بالنتائج المثلى ، يقترح الذكاء الاصطناعي حلول البرمجيات و التي من بينها أدوات متنوعة مثل: التعلم الآلي و ذلك باستخدام العديد من الطرق كاستخراج البيانات من الصور و تحديد البيانات المهمة التي يمكن ان تحدث الفارق في عملية التصنيف باستخدام خوارزميات التصنيف المعروفة . نركز في عملنا هذا لمذكرة الماستر على حل مسائل تصنيف الصور الطبية. الهدف من الدراسة هو تطبيق أساليب اختيار السمات على الصور الطبية، وتحديدا، اختيار السمات ذات الصلة لحل مسائل تصنيف الصور الطبية. تم استخراج أكثر من مائة سمة من الصور. يتم استخدام ثلاث طرق مختلفة لتحديد مجموعات فرعية متكونة من سبع سمات من المجموعة الأصلية. يتم تقييم المجموعات الفرعية التي تم إنشاؤها من خلال أدائها التصنيفي باستخدام خوارزمية التعلم، وأساسًا طريقة Knn (أو باللغة الإنجليزية K-nearest neighbors). يتم التعلم من ثلاث قواعد اختبار كبيرة. أظهرت النتائج التجريبية المتحصل عليها تحسينات معتبرة في أداء التصنيف. ""Abstract: Data Analysis has become more common and widely used in the field of medicine especially in diagnosis and refining research and development tasks of providing the appropriate tools based on the extracted and collected data about diseases. For analyzing data and predicting better results, Artificial Intelligence suggests diffierent programming solutions among them: Machine Learning, and that by employing multiple ways like extracting data from images and then selecting useful ones that should make diffierence when used with the common classification algorithms. In this work we are interested in solving classification problems in the field of medical imaging. The goal is to apply feature selection methods to medical images and more specifically to select the most relevant features to solve medical image classification problems. More than one hundred features are extracted from the images. Three different methods are used to select subsets of seven features from the starting set. The constructed subsets are evaluated by their classification performance using a learning algorithm, mainly the K-nearest neighbor (KNN). The learning is done on three available large datasets. The results obtained from our experiments showed significant improvements in classification performance. "
mémoure master informatique
Keywords: الكلمات المفتاحية: اختيار الميزات، التصنيف، التصوير الطبي، التعلم الآلي ، خوارزمية KNN; Keywords: Feature selections, Classification, Medical imaging, Machine learning, K-nearest neighbor Algorithm